2015
DOI: 10.1038/srep10767
|View full text |Cite
|
Sign up to set email alerts
|

Computing Arm Movements with a Monkey Brainet

Abstract: Traditionally, brain-machine interfaces (BMIs) extract motor commands from a single brain to control the movements of artificial devices. Here, we introduce a Brainet that utilizes very-large-scale brain activity (VLSBA) from two (B2) or three (B3) nonhuman primates to engage in a common motor behaviour. A B2 generated 2D movements of an avatar arm where each monkey contributed equally to X and Y coordinates; or one monkey fully controlled the X-coordinate and the other controlled the Y-coordinate. A B3 produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 42 publications
1
46
0
2
Order By: Relevance
“…With wireless neural recordings and multiple devices, social interaction experiments such as those involving multiple monkeys reaching for the cued reward locations on separate devices can be designed. Such interactions may also be implemented as brain-to-brain interface experiments ( Pais-Vieira, Lebedev et al 2013 ; Pais-Vieira, Chiuffa et al 2015 ; Ramakrishnan, Ifft et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…With wireless neural recordings and multiple devices, social interaction experiments such as those involving multiple monkeys reaching for the cued reward locations on separate devices can be designed. Such interactions may also be implemented as brain-to-brain interface experiments ( Pais-Vieira, Lebedev et al 2013 ; Pais-Vieira, Chiuffa et al 2015 ; Ramakrishnan, Ifft et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A neuroscientist paralysed by amyotrophic lateral sclerosis (ALS; also known as Lou Gehrig's or motor neuron disease) has used a BCI to run his laboratory, write grant applications and send e-mails 3 . Meanwhile, researchers at Duke University in Durham, North Carolina, have shown that three monkeys with electrode implants can operate as a 'brain net' to move an avatar arm collaboratively 4 . These devices can work across thousands of kilometres if the signal is transmitted wirelessly by the Internet.…”
Section: Intelligent Investmentsmentioning
confidence: 99%
“…After decoding, the signals were sent to the virtual arm, with monkeys contributing to coordinates equally (B) or with each monkey controlling only one coordinate (C) or one plane (D). The tasks were performed more effectively compared to the experiment where only one animal controlled the virtual arm (Ramakrishnan et al, [81]). …”
Section: обзор нейроинтерфейсыmentioning
confidence: 99%
“…In general, the task is to create the network that would combine knowledge and effort of several individuals for more effective problem solving. Among such distributed networks are a neuron-net (a community of people and technologies that use neuronal signals for communication), a body-net (a net in which the movements of one individual can be transmitted to another through FES) and a brain-net (an integration of several brains by BCI-technologies [81], fig. 4).…”
Section: Cortical Implantsmentioning
confidence: 99%